On the legal status of an interpreted confession - Cal-Meyer, Pilar; Coulthard, Malcolm (Language and Law / Linguagem e Direito, 2017)
Aifang Ye, a non-English speaking woman, was convicted of making a false statement in a passport application. The conviction was based almost exclusively on a ‘confession’ produced at the end of an investigative interview with an Immigration and Customs Enforcement (ICE) agent that was conducted through an interpreter who was linked by telephone. The written confession was presented to the court solely in English, even though Ms Ye did not understand English and never wrote or spoke any of the words contained in the confession. Despite a request by the defense lawyer, the prosecutor refused to make the interpreter available for cross-examination. The defense, citing the Confrontation Clause of the Sixth Amendment, argued that prosecutorial actions and judicial decisions violated Ms Ye’s rights, on the grounds that the prosecution had failed to make he interpreter available for cross-examination. The case revolves around the question of the status, reliability and output of interpreters – is an interpreter simply a mouthpiece or conduit, or does acting as an interpreter necessarily involve the interpreter in the co-production rather than just the conveying of the message? If the latter, then interpreted and/or translated statements like Ms Ye’s confession which were produced outside the court must be considered to be testimonial hearsay statements, which are inadmissible at trial unless the defense has the possibility to cross-examine the declarant, in Ms Ye’s case the interpreter.